Design of Intelligent Street Lamp System Driven by New Energy Sources - Sun, Zeyu (International Journal of Electric Power and Energy Studies, 2024)
The streets, large and small, are full of street lights, which light up the way home when night falls. But tens of thousands of street lamps consume a lot of energy. The non-renewable energy on the earth is limited, so in order to protect our earth and enable the sustainable development of the earth, this paper designs and develops an intelligent street lamp system driven by new energy sources. Different from the traditional single power supply mode, the street lamp mentioned in this paper uses solar energy, wind energy and ceramic piezoelectric machinery to provide electricity to the street lamp. Solar power is generated when the sun is full, and wind power is generated when there is no sun. The mechanical energy of a car passing through piezoelectric ceramics can also be used to generate electricity in special weather conditions when there is no wind or sunshine. A variety of power generation methods have solved the malpractice of new energy source street lamps relying on weather conditions. And the system can display the power of the storage battery in real time, and light it automatically when night falls. It is an efficient multi-source drive intelligent new energy street lamp.